Effect of Interventricular Electrical Delay on Atrioventricular Optimization for Cardiac Resynchronization Therapy. (August 2018) - Gold, Michael R.; Yu, Yinghong; Singh, Jagmeet P.; Birgersdotter-Green, Ulrika; Stein, Kenneth M.; Wold, Nicholas; Meyer, Timothy E.; Ellenbogen, Kenneth A.
Abstract : Background: Routine atrioventricular optimization (AVO) has not been shown to improve outcomes with cardiac resynchronization therapy (CRT). However, more recently subgroup analyses of multicenter CRT trials have identified electrocardiographic or lead positions associated with benefit from AVO. Therefore, the purpose of this analysis was to evaluate whether interventricular electrical delay modifies the impact of AVO on reverse remodeling with CRT. Methods: This substudy of the SMART-AV trial (SMARTDELAY Determined AV Optimization) included 275 subjects who were randomized to either an electrogram-based AVO (SmartDelay) or nominal atrioventricular delay (120 ms). Interventricular delay was defined as the time between the peaks of the right ventricular (RV) and left ventricular (LV) electrograms (RV-LV duration). CRT response was defined prospectively as a >15% reduction in LV end-systolic volume from implant to 6 months. Results: The cohort was 68% men, with a mean age of 65±11 years and LV ejection fraction of 28±8%. Longer RV-LV durations were significantly associated with CRT response ( P <0.01) for the entire cohort. Moreover, the benefit of AVO increased as RV-LV duration prolonged. At the longest quartile, there was a 4.26× greater odds of a remodeling response compared with nominal atrioventricular delays ( P =0.010). Conclusions: Baseline interventricular delay predicted CRT response. At long RV-LV durations, AVO can increase the likelihood of reverse remodeling with CRT. AVO and LV lead location optimized to maximize interventricular delay may work synergistically to increase CRT response. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00874445.